TDT668: Textile Products / College of Creative Arts - UiTM, College of Creative Arts (2023)
This subject is a common programmed based around studio / workshop practice and personal individual programmed study. It provides technical ability and skill in a variety of ways which reflect contemporary practice in the area of Resist Textile. The subject also recognizes the importance of having a personal and distinctive approach in their final product. This may well involve working with new media or combined elements of practice from printing and fiber textile. Typically projects will concentrate on textiles for fashion, interiors or creative textiles.